Anticipated and imagined futures: prospective cognition and depressed mood following brain injury - Murphy, Fionnuala C. (Br J Clin Psychol, 2018)
OBJECTIVES: Depression, which is common following acquired brain injury (ABI), has been shown to predict cognitive impairment, rehabilitation outcome, and quality of life. Whilst many studies have examined links between depression and cognitive–affective processing in the non‐ABI population, their applicability to this important clinical group, where cognitive difficulties can be marked, remains unknown. Here, we investigated biases in prospective cognition, which is known to be disrupted in (non‐ABI) depression yet important for well‐being. DESIGN: Cross‐sectional design with three groups (depressed ABI, non‐depressed ABI, and non‐ABI control participants). Continuous data were additionally analysed in correlation analyses. METHODS: Individuals with ABI varying in extent of self‐reported depression and matched non‐ABI control participants completed assessments of mood and prospective cognition (anticipating and imagining future events), alongside background tests of executive function and fluid intelligence. RESULTS: Relative to non‐depressed ABI and control participants, depressed ABI individuals demonstrated a reduced positive bias in prospective cognition: whereas non‐depressed ABI and control participants generated more examples of likely or possible positive versus negative future events, there was no evidence for such a positive bias in depressed ABI participants. Non‐depressed ABI and control participants also reported more vivid mental imagery for positive versus negative future scenarios, whereas such a pattern was not evident in depressed ABI participants. This pattern emerged despite background impairments in fluid intelligence and executive function associated with ABI. CONCLUSIONS: These findings (1) elucidate depression‐linked cognitive–affective processes following ABI, where cognitive difficulties are common, and (2) highlight psychological processes associated with depression that are common to ABI and non‐ABI populations. PRACTITIONER POINTS: Clinical implications: A relative negative bias in future‐directed cognition is associated with depressed mood in individuals with chronic ABI. Such processes may contribute to the onset and maintenance of depression following ABI. These findings suggest it may be important to consider a role for prospective cognition in psychological interventions for depression following ABI. Limitations of the study: The extent to which depressed mood following ABI is associated with biases in other cognitive domains remains unclear. Whether similar patterns would be observed in acute patients with more profound cognitive difficulties requires further investigation. Despite large effect sizes, our sample size is modest; these effects thus require replication in larger groups.